PERAN MEDIA PEMBELAJARAN DALAM PROSES BELAJAR MENGAJAR IPA - Vinna Ariyani; Amanda Putri Elysia; Cici Lia Ayu Fatmawati; Intan Dwi Yuswanti; Rizka Elan Fadilah; I Ketut Mahardika; Firdha Yusmar (Pendidikan Fisika FKIP UNEJ, 2022)
Learning Media is a tool so that the teaching and learning process can be achieved smoothly. Learning media is designed to be as attractive as possible to arouse students' learning motivation during the learning process. With interesting media, the learning process will not feel boring. Teaching and learning is supported by learning media so that it runs well. Learning itself has an understanding is a process of behavior change that includes the addition of knowledge and experience of new things. With the aim of learning that so that everyone knows about new things. While teaching is an activity of delivering material during the learning process. In science, the learning is related to natural phenomena and research. The objectives of learning science include products, processes, and scientific developments. Natural sciences (IPA) are generally knowledge obtained from data collection through experimentation, observation, and data analysis to provide explanations for existing phenomena. The purpose of the various science learning models is to provide understanding to students so that it is easier to capture the material that has been given.